Single phase matrix converter for boost inverter operation controlled using Xilinx FPGA / Mohd Hafiz Mohd Nasir - Mohd Nasir, Mohd Hafiz (Universiti Teknologi MARA (UiTM), 2011)
This paper is concerned on FPGA design for control implementations of the Single Phase Matrix Converter (SPMC) operating as a Boost Inverter. The main attribute of the boost inverter topology is the fact that it generates an ac output voltage larger than the dc input voltage depending on the instantaneous duty cycle. The power circuit uses the Insulated Gate Bipolar Transistor (IGBT) as switching device in the SPMC implementation. The Sinusoidal Pulse Width Modulation (SPWM) technique is used to synthesize the output voltage. The selected experimental and simulation results are presented to verify the proposed operation of boost inverter.